Coagulase Activity by Staphylococcus aureus: A Potential Target for Therapy? - Peetermans, Marijke; Verhamme, Peter; Vanassche, Thomas (Seminars in Thrombosis and Hemostasis, 2015)
Staphylococcus aureus is a leading cause of skin and soft tissue infections, foreign body infections, and infective endocarditis. In case of endovascular infection with S. aureus, higher rates of cardiac valve destruction, embolic complications, severe sepsis, and death occur. The unique capacity of S. aureus to induce clotting has been known for over a century; however, its role in virulence has long been controversial. S. aureus secretes two coagulases, staphylocoagulase and von Willebrand factor binding protein that both activate prothrombin to generate fibrin. A better understanding of the molecular mechanisms as well as the new strategies to target the coagulases have highlighted their importance in S. aureus virulence. Coagulase activity is essential for the formation of S. aureus–fibrin–platelet microaggregates and for the homing of S. aureus to the vascular wall under flow. Absence or inhibition of S. aureus coagulase activity improved outcome in disease models of skin infection, sepsis, catheter infection, and endocarditis. Here, we review how the manipulation of the host's hemostatic system contributes to the disease-causing potential of S. aureus and discuss the S. aureus coagulases as promising targets for novel therapeutic strategies.
Keywords: Staphylococcus aureus; staphylocoagulase; von Willebrand factor binding protein; innate immunity